2014
DOI: 10.1051/bioconf/20140301012
|View full text |Cite
|
Sign up to set email alerts
|

Vine spacing on cv. Tempranillo in the Appellation of Origin Cigales (Spain): Agronomy and quality effects

Abstract: Abstract. This paper studies the vegetative, productive and qualitative behavior of the Tempranillo variety, vertically trellised trained, according to a placement of vines with three different distances (1.04, 1.40 and 1.80 meters) in the row and a common distance between rows (2.40 meters), in order to determine the most suitable vine distance for the growing conditions. The experimental test has been developed for the period 2007-2011 in the Appellation of Origin Cigales, in Valladolid (Spain). The reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…The total soluble solids concentration was higher in the density-top treatment, and with a statistically significant difference compared the other treatments. These results are not in agreement compared to results from a previous study [14], in which the study of the plant density of grape cultivar Tempranillo showed that the pH and total soluble solids exhibited no difference between the different plant densities. The result of the present study could be due to that fact that the vines collected from the density-top treatment are located at the top of the slope.…”
Section: Mechanical Properties Of Grapes and Berries And Characters O...contrasting
confidence: 99%
“…The total soluble solids concentration was higher in the density-top treatment, and with a statistically significant difference compared the other treatments. These results are not in agreement compared to results from a previous study [14], in which the study of the plant density of grape cultivar Tempranillo showed that the pH and total soluble solids exhibited no difference between the different plant densities. The result of the present study could be due to that fact that the vines collected from the density-top treatment are located at the top of the slope.…”
Section: Mechanical Properties Of Grapes and Berries And Characters O...contrasting
confidence: 99%